A Research on The Attitudes of Mothers About Rational Drug Use Within the Scope of Patient Safety - Esra Tural Buyuk; Nihal Unaldi Baydin (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Aim: This study was conducted to find out mothers’ attitude about rational drug use within the scope of patient safety. Method: This study was carried out in a university hospital in the North of Turkey between May and June 2019 and the sample consisted of 326 mothers whose children were hospitalized in paediatric services. Characteristics Information Form and Parental Attitude Scale towards Rational Drug Use were used as data collection tool. Number, percentage, average, standard deviation, mean and one way variance analysis test were used to evaluate the data. Results: It was found that 36.5% of the patients were between 26 and 30 years of age and 28.8% were high school graduates. It was found that 84% of the participants used drugs without prescription and 65.3% gave mostly pain killers and antipyretic drugs to their children. Mothers’ average Attitude Scale towards Rational Drug Use score was found as 153.43±28.70. It was found that educational status of mothers affected their parental attitude towards rational drug use (p<0.05). Conclusion: It was found that most of the mothers used drugs without prescription and they mostly gave pain killers and antipyretic drugs to their children. University graduate mothers were found to have high rational drug use attitudes. In ensuring patient safety, it is recommended for nurses to generalize informing activities about mothers’ rational drug use.